Rapid cellular enrichment of eicosapentaenoate after a single intravenous injection of a novel medium-chain triacylglycerol:fish-oil emulsion in humans - Carpentier, Yvon A; Hacquebard, Mirjam; Portois, Laurence; Dupont, Isabelle E; Deckelbaum, Richard J; Malaisse, Willy J (The American journal of clinical nutrition, 2010)
BACKGROUND: Dietary deficiency in n-3 (omega-3) polyunsaturated fatty acids (PUFAs) prevails in Western populations and potentially results in adverse health outcomes. To circumvent the slow n-3 PUFA incorporation in phospholipids of key cells after oral supplementation, a new preparation for intravenous bolus injection was developed with 20 g triacylglycerols/100 mL of a mixture of 80% medium-chain triacylglycerols (MCTs) and 20% fish oil (FO) (wt:wt), and 0.4 g α-tocopherol/100 mL of the same mixture. OBJECTIVE: Our objective was to document the enrichment of n-3 PUFAs in leukocyte and platelet phospholipids after a bolus intravenous injection of MCT:FO in men. DESIGN: Twelve healthy male subjects received injections over a 5-min period of 50 mL of either MCT:FO or a control MCT:long-chain triacylglycerol (MCT:LCT) emulsion containing 20 g triacylglycerols/100 mL with equal amounts (wt:wt) of MCT and soybean triacylglycerols (LCT) and containing 0.02 g α-tocopherol/100 mL; after an 8-wk interval, the subjects received injections of the other preparation. RESULTS: Clinical and biological variables that assessed tolerance and safety remained unchanged. Plasma elimination was faster for MCT:FO than for MCT:LCT (half-life: 24.5 ± 3.5 min compared with 32.9 ± 3.0 min; P < 0.025). This was associated with a greater increase in the plasma nonesterified fatty acid concentration. The content of n-3 PUFAs, specifically eicosapentaenoic acid (20:5n-3), increased in leukocyte and platelet phospholipids within 60 min and ≥24 h after MCT:FO injection. CONCLUSION: Bolus intravenous injection of a novel MCT:FO emulsion allows rapid enrichment of cells with n-3 PUFAs.